Peran Good Corporate Governance, Pertumbuhan Perusahaan dan Keputusan Pendanaan Terhadap Nilai Perusahaan: Profitabilitas Sebagai Variabel Mediasi Pada Perusahaan Sektor Manufaktur: (Studi Pada Jakarta Islamic Index) - Alya, Maulida; Setiawan, Ananda (Eastasouth Institute, 2024)
The purpose of this study was to evaluate the impact of good corporate governance, company growth and funding decisions on the value of companies listed on the Jakarta Islamic Index between 2018-2022. Profitability was included as an intervening variable. Panel data, a type of secondary data, is used in this quantitative study. A sample of 11 businesses that are listed on the Jakarta Islamic Index was derived from the purposive sampling method's outcomes. Processed using Eviews 10 and data analysis methods, including descriptive statistical tests, stationarity tests, F tests, t tests, R2 tests, path analysis and Sobel tests. These findings suggest that while finance choices and profitability have an impact on a business's value, GCG and company growth do not. Then, decisions on funding, firm expansion, and GCG have no bearing on profitability. The relationship between GCG, business growth, and funding decisions on firm value cannot be mediated by profitability.